Bagansiapiapi Youth Center Dengan Pendekatan Arsitektur Ekspresionis - Rizfaldi, Rizki; Susilawaty, Mira Dharma; Hidayat, Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Youth is the time of life when someone considered young and the transition from childhood into maturity, youth experience various changes in both physical and psychic terms. Such changes can be either good or otherwise determined by many factors within themselves and their environment. Their activities and tendencies also affect as part of their changes, such as through doing their hobbies and interests could establish their personality and character in a more positive direction in the future. Bagansiapiapi, which is the capital of the district Rokan Hilir, Riau Province has a population with a large range of teenager age. There are so many youth positive activity, but there are still many of them that have not been facilitated and they finally look for other alternative places or do other activities that maybe unsettling and could harm themselves or others. Therefore, a facility is required intended for the youths to perform their positive activities such as the Youth Center. Youth Center has facilities that can accommodate the youth activities such as sports, arts, education and meetings. As the center of youth activity, Bagansiapiapi Youth Center would implement the style of expressionist architecture. Expressionist architecture is used because one of the principles is to create freely and expression that matches the characteristics of a free and the rebel of youth. Expressionist architecture is expected to translate the soul of the youthful spirit into the tangible design.Keywords : Youth, Youth Center, Expressionist Architecture